Traditional Botanical Treatments for Mycosis Show Promise as Novel Agents for the Treatment of a Variety of Fungal Skin Pathologies - Edwin Cock, Ian (Asian Journal of Biological and Life Sciences)
A recent study published in The FASEB Journal identified a C. sativum leaf component which is a potent activator of KCNQ channels.1 C. sativum leaves (Figure 1) have long been used as anticonvulsants to treat neurological conditions including epilepsy in traditional medicine systems, but their mechanism of action was unknown. The research by the UCI group isolated a lipophilic long chain fatty aldehyde component called dodecanal that binds to KCNQ potassium channels, thereby forcing them to remain open and active. Notably, dodecanal binds several ion channels including the predominant neuronal and cardiac channels. Therefore, dodecanal is not only responsible for the anticonvulsant action of C. sativum leaves but can also regulate cardiac activity. Interestingly, this plant also has several other reported therapeutic properties, including anticancer, antimicrobial and analgesic activities, although these yet to be rigorously examined.